Multilocus Sequence Typing of Serially Collected Isolates of Cryptococcus from HIV-Infected Patients in South Africa - Van Wyk, Marelize (American Society for Microbiology, 2014)
Patients with cryptococcal meningitis in sub-Saharan Africa frequently relapse following treatment. The natural history and etiology of these recurrent episodes warrant investigation. Here, we used multilocus sequence typing (MLST) to compare the molecular genotypes of strains of Cryptococcus neoformans and Cryptococcus gattii isolated from serial episodes of cryptococcal meningitis that were separated by at least 110 days. The most common MLST genotypes among the isolates were the dominant global clinical genotypes (M5 and M4) of molecular type VNI, as well as the VNI genotypes apparently restricted to southern Africa. In addition, there was considerable genetic diversity among these South African isolates, as 15% of the patients had unique genotypes. Eleven percent of the patients were reinfected with a genetically different strain following their initial diagnosis and treatment. However, the majority of serial episodes (89%) were caused by strains with the same genotype as the original strain. These results indicate that serial episodes of cryptococcosis in South Africa are frequently associated with persistence or relapse of the original infection. Using a reference broth microdilution method, we found that the serial isolates of 11% of the patients infected with strains of C. neoformans var. grubii with identical genotypes exhibited ≥4-fold increases in the MICs to fluconazole. Therefore, these recurrent episodes may have been precipitated by inadequate induction or consolidation of antifungal treatment and occasionally may have been due to increased resistance to fluconazole, which may have developed during the chronic infection.